Antihyperlipidemic effect of Trichilia connaroides in hypercholesterolemic rats and its possible mechanism - Prasanna Gurunath Subbarao; Purnima Ashok (Wolters Kluwer Medknow Publications, 2011)
Objectives: The primary objective of this study was to investigate the antihyperlipidemic effect of the chloroform (CETC) and methanol (METC) extracts of leaves of Trichilia connaroides in hypercholesterolemic rats and, subsequently, to evaluate the possible mechanism of its antihyperlipidemic effect. Materials and Methods: The antihyperlipidemic activity of CETC and METC (100 mg/kg) in hypercholesterolemic rats was investigated by recording the serum lipid profile after a month-long oral treatment of these extracts. Further, hypercholesterolemic regression test and hypercholesterolemic progression test were carried out to understand the possible mechanism of its antihypercholesterolemic effect. The data were analyzed for statistical significance by one-way ANOVA, followed by Dunnet's test. Results and Conclusion: Hypercholesterolemic rats treated with CETC and METC produced a significant fall (P<0.05) in plasma triglyceride, total cholesterol, very low density lipoprotein (VLDL )-cholesterol and low density lipoprotein (LDL)-cholesterol and rise (P < 0.05) in high density lipoprotein (HDL) -cholesterol. A significant reduction (P < 0.01) in atherogenic index, increase (P < 0.05) in body weight and an insignificant influence on food intake were also observed at the end of the study. A hypercholesterolemic regression test revealed a significant reduction (P < 0.05) in the serum cholesterol level in both CETC and METC extract-treated animals. During the hypercholesterolemic progression test, a similar reduction in the serum cholesterol level was observed only in the METC extract-treated animals. The antihyperlipidemic effect was similar to fenofibrate and ezitimibe. Significant changes in the lipid profile in hypercholesterolemic animals confirm a potential antihyperlipidemic activity of the extracts. The CETC and METC extracts influenced the absorption and metabolism of dietary cholesterol to elicit the antihyperlipidemic effect.